In vitro clonal propagation of BARI Ada-1 (Zingiber officinale Rosc.) - Yesmin, S; Hashem, A; Khatun, MM; Nasrin, S; Tanny, T; Islam, MS (Jahangirnagar University Journal of Biological Sciences, 2016)
Abstract not available Jahangirnagar University J. Biol. Sci. 4(2): 53-57, 2015 (December)